A Historical Account of Linguistic Imperialism and Educational Policy in Tunisia: From the independence to the ‘Jasmine Revolution’ - Leila Najeh Bel’Kiry (Indonesian TESOL Journal, 2021)
This article is about foreign languages hegemony in Tunisia. It describes the linguistic situation at the macro and micro levels, the Tunisian and the international linguistic communities, the status of English and French languages throughout the world, and their effects on the Tunisian educational policy. The prevalence of French in Tunisia as the language of science and technology between 1956 and 1987, the way the  value of English is promoted in the Tunisian educational system between 1987 and 2011 though Tunisia is a French colonized country, and the tendency to linguistic isolationism since 2011, prove the intrinsic link between language and politics. Political changes at international and local levels shape the local linguistic communities.